The constructions of terrorism: an interdisciplinary approach to research and policy - Stohl, Michael; Burchill, Richard; Englund, Scott (University of California Press, 2017)
Introduction: constructions of terrorism / Michael Stohl, Scott Englund, and Richard Burchill -- Can terrorism be defined? / Lisa Stampnitzky -- Misoverestimating terrorism / John Mueller and Mark G. Stewart -- Terrorism as tactic / David H. Schanzer -- The construction of state terrorism / Ruth Blakeley -- Killing before an audience: terrorism as performance violence / Mark Juergensmeyer -- Constructing terrorism: from fear and coercion to anger and jujitsu politics / Clark McCauley -- Framing terrorism: the communicative constitution of the terrorist actor / Benjamin K. Smith, Scott Englund, Andrea Figueroa-Caballero, and Michael Stohl -- Some thoughts on constructions of terrorism and the framing of the terrorist threat in the UK / Anthony Richards -- Contradictions in the terrorist discourse and constraints on the political imagination of violence / Richard Falk -- Legal constructions of terrorism / Richard Burchill -- Do different definitions of terrorism alter its causal story? / Rachel Levin and Victor Asal -- Analyzing pathways of lone-actor radicalization: a relational approach / Stefan Malthaner and Lasse Lindekilde -- Constructing cultures of martyrdom across religions, time, and space / Mia Bloom -- Introducing Government Actions in Terror Environments (GATE) dataset / Laura Dugan and Erica Chenoweth -- The world vs. Daesh: constructing a contemporary terrorist threat / Scott Englund and Michael Stohl -- Conclusion, understanding how terrorism is constructed / Michael Stohl, Scott Englund, and Richard Burchill